Anteseden Perilaku Rencana Keuangan Mahasiswa - Maftazanah, Shifa (tesco publisher, 2023)
The purpose of this research is to analyze the influence of self-control, lifestyle, social environment, and intellectual intelligence on the financial planning of Accounting students. This research is a quantitative research employing convenience sampling techniques for sample selection. Population in this research has involved all active students of Accounting major, Faculty of Economic and Business at Jenderal Soedirman University who are enrolled in the year 2018-2022. The total utilized sample size in this research is 100 respondents. The research data source consists of primary data, and data collection is conducted through the utilization of a questionnaire. Data is processed is analyze using multiple regression analysis with the assistance of SPSS software version 26. The findings of the research revealed that self-control and intellectual intelligence has a impact on improving financial planning among accounting students. Meanwhile, lifestyle and social environment does not have an influence on improving financial planning among accounting students.